A phage-displayed single chain variable fragment that interacts with hepatitis B core antigen: Library construction, selection and diagnosis - Tan, Geok Hun; Yusoff, Khatijah; Seow, Heng Fong; Tan, Wen Siang (Elsevier, 2007)

(untitled)
Background Phage display is an alternative method for constructing and selecting antibodies with desired specificity towards an antigen.